A Study of Manifestations of Extrapulmonary Tuberculosis in the ENT Region - Akkara, Stani Ajay (Springer India, 2013)
Though tuberculosis (TB) primarily affects lungs, extra pulmonary tuberculosis (EPTB) is also common, especially in high disease load areas and mainly manifests in ENT region. To study the different manifestations of tuberculosis in ENT region in terms of presentation, disease process, treatment and outcome. Records of patients diagnosed and treated for TB in the ENT region at our institute’s DOTS centre for a two and half year period were analysed for presenting complaints, examination findings, diagnostic features, treatment modes and outcome. Out of 3750 cases diagnosed as TB, 230 had EPTB. 211 cases had ENT manifestations. Majority of the cases were male and in the fourth decade of life. Commonest manifestation was cervical lymphadenopathy with 201 cases. Fine needle aspiration cytology was mostly diagnostic and category I anti TB treatment (AKT) achieved cure. The six cases of TB otitis media presented with ear discharge, sometimes bloody and had varied tympanic membrane findings and facial palsy in two cases with different types and degrees of hearing loss. Diagnosis was confirmed by histology of tissue removed during surgery. Patients completed category I AKT. Hearing and facial palsy did not improve. There were three cases of TB laryngitis and one of nasal TB both of which were confirmed by tissue diagnosis and responded well to AKT. Most of the results in the present study conform to findings of other studies. High degree of suspicion is necessary to reach diagnosis. Category I AKT is effective. Some cases may require surgery.